European eel in the Mediterranean Sea – Outcomes of the GFCM Research programme - E. Ciccotti; E. Morello (Food and Agriculture Organization of the United Nations, 2023)
In line with the provisions of Recommendation GFCM/42/2018/1 on a multiannual management plan for European eel in the Mediterranean Sea and on the basis of the discussions held at the 2018 Working Group on the management of European eel, a GFCM research programme on European eel (Anguilla anguilla) was carried out from 2020 to 2022. Divided into five work packages, it was executed as a concerted action joining the forces of ongoing research conducted by research institutes, universities and the relevant administrations of nine partner countries (Algeria, Albania, Egypt, France, Greece, Italy, Spain, Tunisia and Türkiye). The main aim of the research programme was to devise a coordinated framework for the collection and analysis of data, as well as for the assessment and management of the resource, with a view to laying the groundwork for a long-term, multiannual management plan for European eel in the Mediterranean. The research programme enabled the collection of data and information on management and protection measures for stock recovery at both the national and local levels, as well as on eel fisheries and eel habitats and the biological and ecological features of local eel stocks. Meanwhile, it also established a common framework for assessing European eel stocks at different scales in the Mediterranean. This publication compiles and presents the results of the analyses carried out, together with the data collected, within the framework of this research programme, and it provides the scientific basis for advice on fishery management measures towards the recovery of eel stocks, using the evidence collected as a foundation for action tailored to the Mediterranean scenario.